Effects of low-fat or full-fat fermented and non-fermented dairy foods on selected cardiovascular biomarkers in overweight adults. Issue 12 (12th June 2013) - Nestel, Paul J.; Mellett, Natalie; Pally, Suzana; Wong, Gerard; Barlow, Chris K.; Croft, Kevin; Mori, Trevor A.; Meikle, Peter J.
Abstract : The association between consumption of full-fat dairy foods and CVD may depend partly on the nature of products and may not apply to low-fat dairy foods. Increased circulating levels of inflammatory biomarkers after consumption of dairy product-rich meals suggest an association with CVD. In the present study, we tested the effects of low-fat and full-fat dairy diets on biomarkers associated with inflammation, oxidative stress or atherogenesis and on plasma lipid classes. Within full-fat dairy diets, we also compared fermented v . non-fermented products. In a randomised cross-over study, twelve overweight/obese subjects consumed during two 3-week periods two full-fat dairy diets containing either yogurt plus cheese (fermented) or butter, cream and ice cream (non-fermented) or a low-fat milk plus yogurt diet, with the latter being consumed between and at the end of the full-fat dairy dietary periods. The concentrations of six inflammatory and two atherogenic biomarkers known to be raised in CVD were measured as well as those of plasma F2 -isoprostanes and lipid classes. The concentrations of six of the eight biomarkers tended to be higher on consumption of the low-fat dairy diet than on that of the fermented dairy diet and the concentrations of two plasmalogen lipid classes reported to be associated with increased oxidisability were also higher on consumption of the low-fat dairy diet than on that of the fermented dairy diet ( P < 0·001), although plasma F2 -isoprostane concentrations did not differ on consumption of any of the diets. On the other hand, the concentrations of plasma sphingomyelin and IL-6 were significantly higher on consumption of the non-fermented dairy diet than on that of the low-fat dairy diet ( P < 0·02). In conclusion, short-term diets containing low-fat dairy products did not lead to a more favourable biomarker profile associated with CVD risk compared with the full-fat dairy products, suggesting that full-fat fermented dairy products may be the more favourable.